Cross Road Elections: Change in EU Performance Evaluations during the European Parliament Elections 2014 - de Vreese, Claes (2016)
The 2014 European Parliament (EP) elections were held after a period where public opinion about the EU changed significantly. In this paper we investigate evaluations of the performance of the European Union, as this dimension of EU attitudes is particularly relevant ahead of elections. We look at public opinion developments since 2009 and then zoom in on the role played by the news media in shaping public opinion about EU performance by linking citizens’ evaluations across time to the news media content they were exposed to. The article relies on original multiple wave survey panel data and a systematic media content analysis in the Netherlands. It shows how public opinion has changed, how it changes around EP elections, and how exposure to media coverage can help improve citizens’ evaluations of EU performance.